Impact of the biomolecular corona on the structure of PEGylated liposomes. (5th July 2017) - Digiacomo, Luca; Pozzi, Daniela; Amenitsch, Heinz; Caracciolo, Giulio
Abstract : Protein corona affects the bilayer structure of PEGylated cationic liposomes thus promoting the formation of multilamellar complexes and particle aggregation. Abstract : Driven by the promises of gene therapy, PEGylated cationic liposomes (CLs) have been investigated for decades, but their use in the clinical setting is far from established. Such a dichotomy is due to several factors that have been ignored over the last two decades. The hardest challenge seems to occur when PEGylated CLs come into contact with a physiological environment ( e.g. the blood). Recent evidence has demonstrated that PEGylation does not completely prevent protein binding (as believed so far), but a biomolecular shell, termed "biomolecular corona" (BC), covers the liposome surface. Here we show that the formation of a BC not only affects the surface properties of PEGylated CLs, but also, and significantly, their bilayer structure thus impairing their ability to safely deliver their cargo to the target site. Therefore, a mechanistic understanding of the structures emerging from liposome–protein interactions may represent a truly new paradigm for the clinical translation of PEGylated CLs.